Intercultural values on School System The Italian case - Minello, Rita; Raffaghelli, Juliana (Formazione & insegnamento, 2015)
The objective of this article is to provide a framework for reflection on the prospects of intercultural education, by taking into account the recent changes in education and teaching, based on information provided by National Ministry, but also the growth of the intrinsic sensitivity of teachers in Italy, which have oriented the choices of institutes, extolling the logic of “Autonomia” (Italian law that regulates the process of schooling system decentralization).